1996
DOI: 10.1021/np960422f
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory Activity of Coumarins fromSantolina oblongifolia

Abstract: Four coumarins were isolated from the EtOAc extract of the flower-tops of Santolina oblongifolia Boiss. (Compositae). They were identified as 7-methoxycoumarin (herniarin) (1), 6,7-dihydroxycoumarin (aesculetin) (2), 6-methoxy-7-glucosidylcoumarin (scopolin) (3), and 6-hydroxy-7-methoxycoumarin (scopoletin) (4). This is the first report of the isolation of aesculetin and scopolin from the genus Santolina. The isolated coumarins showed marked activity as inhibitors of eicosanoid-release from ionophore-stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(59 citation statements)
references
References 22 publications
1
55
0
3
Order By: Relevance
“…7-Methoxycoumarin (herniarin, 4), a bioactive coumarin derivative, has shown several important biological activities (Askari et al 2009), including marked anti-inflammatory activity, as an inhibitor of the eicosanoid-release from ionophore-stimulated mouse peritoneal macrophages (Silván et al 1996).…”
Section: Resultsmentioning
confidence: 99%
“…7-Methoxycoumarin (herniarin, 4), a bioactive coumarin derivative, has shown several important biological activities (Askari et al 2009), including marked anti-inflammatory activity, as an inhibitor of the eicosanoid-release from ionophore-stimulated mouse peritoneal macrophages (Silván et al 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Coumarins and their derivatives have been found to exhibit a variety of biological and pharmacological activities and have raised considerable interest because of their potential beneficial effects on human health 11 . They have been reported to possess among others: antibiotic 12 , antibacterials 13 , antitumor 14 , antiviral agents [15][16][17] , anticoagulants 18,19 , against psoriasis 20 , antioxidant 21 , anticancer 22,23 , anti-inflammatory [24][25][26] , analgesic 27 and…”
Section: Introductionmentioning
confidence: 99%
“…No cytotoxicity was apparent when the concentration of a coumarin derivative was less than 1:0 Â 10 À4 M. Coumarins inhibited IgE-mediated histamine release from RBL-2H3 cells as well as that of -hexosaminidase release (data not shown). Coumarin derivatives occur in various spice plants, and have been reported to have antitumoral, 15) fungicidal 16) and anti-inflammatory 17) activities. Although Ryu et al 18) have reported that cnidicin, a coumarin derivative, inhibited mast cell degranulation, degranulation inhibiting activity of 7-methoxycoumarin has not previously been reported.…”
Section: Resultsmentioning
confidence: 99%